A Digital and Paper-free Customs - La Noire Núñez, José Antonio (2019)
The era of Digital Customs is based on a paperless Customs due to the use of technologies to replace paper as a fundamental requirement to exercise its customs authority and offer a service with international standards. In other words, it is the change of mentality, progressively, of all the foreign trade operators that make up the logistics chain. This change began to be implemented since 2012 with the “Customs Dispatch System” (CDS) Project and to date has 3 components: SEIDA (Electronic System for the Exchange of Customs Documents): This allows the various operators to electronically transmit their different transactions. Operator Portal (Internet): Is an interoperability component between customs and foreign trade operators through the SOL key. Customs Officer Portal (Intranet): Where specialists, customs officers and unit heads interact with workflows and manage their operations portfolio.